GWAS identifies 14 loci for device-measured physical activity and sleep duration - Aiden Doherty (Nature Portfolio, 2018)
Studying the genetic underpinnings of physical activity and sleep duration can be confounded by self-reporting. Here, Doherty et al. use data from 91,105 UK Biobank participants, whose activity had been monitored for a week by a wearable device, for genome-wide association analysis and identify 14 loci.